INTRODUCING INDONESIAN LANGUAGE TO THE WORLD THROUGH CULTURE-ENRICHED BIPA LEARNING - Wirawan, Abdul Karim; Nakti, Esa Kharisma Muhammad (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This study aims to introduce the Indonesian language and culture to the world through cultural-based BIPA (Indonesian Language for Foreign Speakers) learning. The method used is content analysis to identify the cultural-based materials in BIPA learning related to Indonesian culture such as customs, arts, music, dance, and culinary. The results of the study show that cultural-based BIPA learning can effectively introduce the Indonesian language and culture to the world. The cultural-based materials in BIPA learning can increase the interest and understanding of the world towards the Indonesian language and culture. Therefore, cultural-based BIPA learning needs to be developed and disseminated widely to introduce the Indonesian language and culture to the world.